Characterization of high electron mobility transistor (HEMT) / Mohd Nazli Mohd Nushi - Mohd Nushi, Mohd Nazli (2008)
In this project, we shall attempt to reproduce simultaneously the DC and RF characteristics of the HEMT using a unique set of physical device parameters. The technology that used in this project is equal to 0.5 urn In this report, a DC models for HEMT's will be represented. This included the Id-Vg characteristics and other topics related to the performance of DC HEMT. Then the RF characteristics for HEMT also discussed in this report. The procedure allows important parameters used, including the donor concentration, doped layer thickness, spacer layer thickness, physical gate length, source resistance, drain resistance, and the saturated electron velocity in the two dimensional electron gas (2DEG) and in the doped AlGaAs to be obtained. Finally, all the result and models including DC model, AC model, velocity-field model for 2DEG and also phenomenological mobility modeling for HEMT are obtained at the end of the project. The DC model (Id-Vg characteristic) then will be compared with result from Silvaco to measure the accurateness of the model. There are slightly different between the result from the theoretical (Python) and Silvaco. In addition, the result from Silvaco is much more accurate compare with the theoretical because there is some element that does not contained in the theoretical part liked temperature, pressure, humidity, types of fabrication and others. Some improvement can be made to the HEMT. By reducing the gate length, it will provide better RF characteristics for HEMT. The future HEMT can improve all the characteristics of HEMT to make the devices give the best performance due to the applications.